Pengembangan Perangkat Pembelajaran Lingkungan Berbasis Potensi Lokal dan Sikap Konservasi - Nike Anggraini; Eka Ad’hiya; Puspa Ayu Pitayati; Khoiron Nazip (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Learning tools based on local potential are prepared by knowing whether or not there is local potential in the South Sumatra region to then be used as a learning resource. This research aims to develop learning tools based on local potential and conservation attitudes for students of the Biology Education Study Program, Faculty of Teacher Training and Education, Sriwijaya University. This research is development research (research and development). The research model refers to the Lee & Owens development model (Analysis, Design, Development, Implementation, and Evaluation). The design stage produces a needs analysis to design the learning tools that will be used. The development stage was carried out to produce learning tools that had been validated by 2 lecturers teaching environmental science courses. Limited trials were carried out on Palembang class students who taught environmental courses. Based on the research results, environmental learning tools have very valid, effective and practical criteria, so they can be implemented in learning.